A STUDY TO FIND OUT THE KEY PARAMETERS AFFECTING THE QUALITY OF EDUCATION IN A TECHNICAL INSTITUTE (International Journal of Engineering Sciences & Management Research, 2016)
Quality Function Deployment is one of the best management tools of TQM. QFD helps in come across the customer’s needs and requirements before actually delivering the product or service to the customer. This paper is based on the review of various literatures, research papers and study in a technical institute. Having a basic part of QFD in education, the purpose of this paper is to identify the technical parameters towards the fulfillment of customer’s (student) requirements obtained through the questionnaire in respect to improve the quality of education in a technical institute.